1999
DOI: 10.1101/gad.13.10.1246
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for Atm in suppressing V(D)J recombination-driven thymic lymphoma

Abstract: Chromosome translocations involving T cell receptor (TCR) loci have been found in tumors from Ataxia telangiectasia (AT) patients and in mouse Atm−/− thymoma, suggesting the involvement of V(D)J recombination in these malignancies. By introducing a RAG-1 deficiency into Atm −/− mice in the presence of a TCR transgene, we show that V(D)J recombination is critical for thymoma development in these mice. Therefore, aberrant V(D)J recombination, normally suppressed by Atm, facilitates tumorigenic events leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…Two possibilities are as follows: a unique role of Atm in lymphoid lineages or a specific lack of redundant pathways to Atm in lymphoid tissue, which would expose the vulnerability of Atm loss. Liao and Van Dyke (43) concluded that there were two different mechanisms of tumor suppression by Atm and p53. Lymphoma suppression in Atm-null mice depended on V(D)J recombination, whereas lymphomas from p53-null mice arose independent of V(D)J recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Two possibilities are as follows: a unique role of Atm in lymphoid lineages or a specific lack of redundant pathways to Atm in lymphoid tissue, which would expose the vulnerability of Atm loss. Liao and Van Dyke (43) concluded that there were two different mechanisms of tumor suppression by Atm and p53. Lymphoma suppression in Atm-null mice depended on V(D)J recombination, whereas lymphomas from p53-null mice arose independent of V(D)J recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Rag À / À Atm À / À mice do not develop leukemia, underscoring the importance of recombination to Atm À / À leukemogenesis. 25 Bid has been reported to be important for cell death in DN3 thymocytes. 27 Bid transcription is stimulated by p53 in DN3 cells.…”
Section: Loss Of Bid Attenuates Leukemia Development Inmentioning
confidence: 99%
“…Loss of the Rag recombinase abrogates leukemia development in Atm À / À mice. 25 We reasoned that if Bid has a pro-apoptotic role in the Atm-directed DDR, loss of Bid in addition to Atm might accelerate leukemogenesis by allowing propagation of oncogenic mutations. If Bid functions solely as an Atm effector, Bid À / À Atm À / À mice should phenocopy Atm À / À mice.…”
mentioning
confidence: 99%
“…In this regard, deficiency in the ataxia telangiectasia mutated (ATM) serine threonine kinase in both mice and humans leads to an increased incidence of lymphoid tumors with RAG-dependent translocations involving antigen receptor loci (17)(18)(19)(20)(21). In addition, mature, nontransformed Atm-deficient lymphocytes have an increased frequency of translocations and other chromosomal aberrations involving antigen receptor loci (18,19,(22)(23)(24).…”
mentioning
confidence: 99%